The post pandemic prospects of work from home in banks in the Republic North Macedonia - Maja Stevkova Shterieva (University American College Skopje, 2021)
The modern banking has never been exposed to event similar to the pandemic of Covid 19 and the massive disruption in different areas of operations due to this event. Until actual health crisis, within their regular activities the banks performed different stress test scenarios including continuity planning as a measure of providing normal operations. The human factor has never been under particular observation in terms of organizational changes that have to been done in case of potentially massive unavailability of working force, as well as its deployment in safe environment. In the attempt to contain the spread of the virus physical or social distancing recommendations were implemented, that resulted with temporary working from home or alternative working arrangements. The aim of the paper is to discuss the challenges of introducing working from home, such as different aspects of telecommuting and the historical perspective of past attempts for this organizational model. Hence, the paper will elaborate the advantages and disadvantages of work from home, as well as post covid prospective. It focuses on the aspect of physical dimension of work, comparing banking with other sectors, operations that can be done remotely, physical presence dependable operations and factors influencing these segmentations. Relevant literature indicate that there are high expectations about accepting work from home or using the hybrid model in the post covid period. A survey with bank management participants was carried out, using questionnaires as a method of data collection. The survey presents how telecommuting is perceived in terms of productivity, scale of absenteeism and reduction of cost, value added to the bank operations and other important aspects of telecommuting. It is exploring the potential and expectations of the banks in North Macedonia for potential introduction of post-pandemic work from home.
Keywords: 330; pandemic; telecommuting; work from home; organisation; banks